BLOCKED CORONARY ARTERY DUE TO CORONARY SPASM TREATED WITH STENT INSERTION: A SUB-OPTIMAL RESULT? - Khan, Habib Rehman; Aslam, Sajid (Journal of Ayub Medical College Abbottabad, 2017)
Myocardial infarction (MI) is an extremely common cause of chest pain. MI can be acute with ST elevation (STEMI) or non-STEMI (NSTEMI). Coronary artery spasm can be severe enough to cause occlusion of the coronary arteries particularly with an exaggerated response in regions of coronary atheroma and plaque ulceration. It is not uncommon for coronary spasm to be mistaken with acute thrombotic occlusion of the coronary artery. We describe a case of a 42-year old man with known cardiac risk factors presents with chest pain for few hours to a tertiary centre hospital. A coronary angiogram showed occlusion of the right epicardial coronary artery with a severe spasm at the level of the atheroma. The initial coronary stent which was deformed because of intense pressure of spasm required another stent to be placed within the first stent. Diltiazem and Nitrates were started as secondary prevention treatment to reduce effect of coronary spasm. The patient made an uneventful recovery and was discharged home with no sequelae over the next 3 years follow up. Keywords: Myocardial infarction; Coronary angiogram; Coronary spasm; Stent